Essays on asymmetric fiscal and monetary policy - Shadmani, Hedieh (Kansas State University, 2015)
This dissertation consists of three essays on modeling the behavior of both fiscal and monetary policy by allowing for asymmetry in preferences of the policy authorities. Whether the responses of fiscal or monetary policy to the business cycle conditions are symmetric or asymmetric is still an unresolved question. The idea behind asymmetric behavior is that policy makers take stronger action during times of distress than during ordinary times. The following chapters investigate this question empirically using data for the United States and show that policy makers do behave asymmetrically. Chapter 1 investigates whether the asymmetric monetary policy preferences for the output gap as shown in Surico (2007) disappeared during the post-Volcker period spanning 1982:04- 2003:02. The results show Surico’s conclusion to be fragile as moving the starting period for the estimation a few quarters forward shows strong asymmetric policy behavior. Chapter 2 investigates U.S. fiscal policy sustainability and cyclicality in empirical structures that allow fiscal policy responses to exhibit asymmetric behavior. Two quarterly intervals of data are investigated, both of which begin in 1955. The short sample was chosen for comparison to Bohn (1998), while the full sample uses all available data. The results for a short sample that ends in the second quarter of 1995 show some differences from the results for the full sample that includes the financial crisis and the Great Recession. For the full sample, U.S. fiscal policy is asymmetrical in regard to both sustainability and cyclicality. Regarding fiscal policy sustainability, the best fitting models show evidence of fiscal policy sustainability for the short sample. However, the fiscal sustainability question does become less clear for the full sample. Regarding fiscal policy cyclicality, we find during times of distress, policy is strongly countercyclical, but during good times the results are mixed. Chapter 3 investigates the source of asymmetry in reaction of U.S. fiscal policy to business cycle conditions, as shown in chapter 2. By decomposing the fiscal policy variable into the tax revenues and the expenditures, we show that both series exhibit asymmetry in a way which is analogous to the results found in chapter 2.
Keywords: Optimal monetary policy; Asymmetric monetary preferences; Asymmetric fiscal policy; Fiscal policy sustainability; Cyclicality; Government expenditure and tax revenues; Economics (0501)